Bis(acetato-κ2 O,O')(4,4′-dimethyl-2,2′- bipyridine-κ2 N,N')zinc - Harvey, M.A. (2012)
The molecular structure of the title compound, [Zn(CH3COO) 2(C12H12N2)], consists of isolated molecules bisected by a twofold rotation axis which goes through the ZnII cation and halves the organic base through the central C-C bond. The Zn II ion is coordinated by two N atoms from one molecule of the aromatic base and four O atoms from two bidentate, symmetry-related acetate anions, which coordinate asymmetrically [Zn-O distances of 2.058(2) and 2.362(3)Å], while the two Zn-N bond distances are equal as imposed by symmetry [2.079(2)Å]. The crystal structure is supported by a number of weak C-H⋯O interactions and C-H⋯π contacts, with no π-π interactions present, mainly hindered by the substituent methyl groups and the relative molecular orientation. The result is a three-dimensional structure in which each molecule is linked to eight different neighbors.